Training Information System at PT. Teknik Media Utama Banda Aceh City - Chandra Bayu Aji (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2021)
The aim of this research is; 1) To find out the training information system at PT. Banda Aceh Main Media Engineering, and 2) To design a training information system at PT. Teknik Media Utama Banda Aceh City. FlowMap and data flow diagrams are used to show the general structure of an information. While the application development process using the waterfall model proposes a systematic and sequential approach to software development that starts at the level and progress of the system throughout analysis, design, code, testing, and maintenance. The research results include; 1) Management of training participant database at PT. Teknik Media Utama is ready to replace the old system gradually in a certain parallel period (4-6 months). During that time, the old system is still used to maintain data security and integrity if an error occurs in the new system, 2) The system will be very helpful for users or data managers of trainees at PT. Teknik Media Utama more quickly, easily and accurately in every activity related to training participant data, and 3) The system is very user friendly and in accordance with the needs of the object. Because in designing designs and others, the author does not design based on personal but always consults with users.